Monte carlo calculations of ultrasound scattering by blood - COBET, Ulrich; KLEMENZ, Albrecht; MILLNER, Rudolf (Archives of Acoustics, 1984)
The ultrasound scattering by blood depends on the flow velocity profile, as can be shown by frequency analysis of the c.w. Doppler signals. Also, the amplitude of the Doppler signals received fluctuates relatively strongly. This, fact cannot be explained completely with the random distribution of single erythrocytes or with noise sources in the signal processing unit. These effects can be understood assuming erythrocyte aggregations in blood. Using the Monte Carlo method we calculate differential scattering cross-sections of blood under the assumption of empirical distributions of aggregates. We will present auto-correlation functions for the ultrasound. scattering by erythrocyte-aggregates, taking into account geometrical effects.